Huge epiglottic cyst: a rare cause of airway obstruction in an adolescent. (1st October 2016) - Chang, Chih-Chen; Lee, Li-Ang; Hsia, Shao-Hsuan; Hsueh, Chuen; Wang, Chao-Jan
Abstract : A 15-year-old boy presented with airway obstruction and a history of sore throat and progressive dyspnoea for 1 month. A lateral neck radiograph showed an enlarged epiglottis, and a neck computed tomography (CT) demonstrated a cyst attached to the lingual surface of the epiglottis. A large epiglottic cyst, 4 cm in length, was removed surgically. Epiglottic cysts have been reported to cause airway obstruction in neonates, infants and adults, but, to the best of our knowledge, it has rarely been reported in adolescents.